Do Muslim Investors Consider Sharia literacy in Their Behavior When Trading Stocks? Experiences of Indonesian Stock Investors : Experiences of Indonesian Stock Investors - Haris, Helmi; Aligarh, Frank (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
The purpose of this study is to explain how the economic behavior of the Indonesian Muslim community in stock transactions influenced by their understanding of sharia. This research uses the Theory of Planned Behavior with exogenous variables being attitude, subjective norm, and perceived behavior control as predictors of intention as the endogenous variable. The ethical domain in this study is indicated by the presence of sharia literacy as a consideration in economic behavior. This research uses a quantitative approach with primary data obtained by distributing questionnaires to respondents who are sharia stock investors in Indonesia. The number of valid questionnaires amounted to 499. The data were processed using Partial Least Squares (PLS) with SmartPLS software. The results of this study show that each of the variables of attitude, subjective norm, and perceived behavior control has a significant positive effect on the intention to invest in sharia stocks. Sharia literacy is proven to moderate the influence of attitude on behavioral intention, but this does not occur in the variables of subjective norm and perceived behavior control.